Deterioration mechanism and dynamic constitutive model of coal-rock assemblages considering chemical corrosion and impact damage - Jianhang Chen; Banquan Zeng; Wuyan Xu; Kun Wang; Peng Liu; Songsong Hu; Shiji Wang; Zhixiang Song; Shaokang Wu; Xuyang Bai (International Journal of Mining Science and Technology, 2025)
To reveal the deterioration mechanism of coal-rock assemblages under chemical corrosion and dynamic loading, chemical corrosion and dynamic impact experiments were conducted. Under different chemical corrosion conditions, the weakening characteristics, observable characteristics, softening characteristics of the dynamic parameters, dynamic failure characteristics, dynamic failure forms and dynamic microscopic characteristics were analyzed. Under each corrosion condition, the dynamic elastic modulus, dynamic deformation modulus and dynamic peak intensity tended to decrease with immersing time. The dynamic elastic modulus, dynamic deformation modulus and dynamic peak intensity exhibited an inverted U-shaped trend. Under dynamic impact, the failure process of acidly corroded samples can be divided into the following stages: the initial stage, elastic energy accumulation stage, local failure of coal and secondary rock crack expansion stage, coal fragment ejection stage, rock spalling stage and complete instability stage. Under dynamic impact, failure modes exist: coal crushing failure, rock fragmenting failure, rock splitting failure and full splitting failure. After impact failure, sample fragments are distributed in powder, granular, cone and block forms. Based on Zhu-Wang-Tang nonlinear viscoelastic properties, a model considering chemical corrosion and impact damage was proposed. The combined effects of chemical and impact-induced damage on the dynamic mechanical properties of coal-rock assemblages were systematically analyzed.